2011
DOI: 10.1002/j.0022-0337.2011.75.12.tb05214.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Haptics to Predict Preclinic Operative Dentistry Performance and Perceptual Ability

Abstract: The aim of this study was to test whether performance on a range of manual dexterity haptic simulator exercises was associated with preclinical operative dentistry examination and Perceptual Ability Test (PAT) scores. Thirty-nine first-year dental students were tested with three haptic exercises-straight line, circle, and mirror line-each performed twice. Haptic exercise outcomes for accuracy, time, and success rate were measured using commercially available computer software. Spearman correlation coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 14 publications
2
49
0
Order By: Relevance
“…The results of this study showed a strong association between pre-and post-test scores of GMS and between pre-and post test scores of the BDT spatial reasoning tests. This shows that the use of both hapTEL and Phantom-head simulator systems improved certain psychomotor skills, spatial awareness and 3D/depth perception over a 3-month period which supports the previous findings by Suksudaj (2010) and Urbankova and Engebretson (2011), that the use of virtual reality simulators can provide a better psychomotor learning through the specific dental programme.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study showed a strong association between pre-and post-test scores of GMS and between pre-and post test scores of the BDT spatial reasoning tests. This shows that the use of both hapTEL and Phantom-head simulator systems improved certain psychomotor skills, spatial awareness and 3D/depth perception over a 3-month period which supports the previous findings by Suksudaj (2010) and Urbankova and Engebretson (2011), that the use of virtual reality simulators can provide a better psychomotor learning through the specific dental programme.…”
Section: Discussionsupporting
confidence: 89%
“…These psychometric tests can be used as a baseline measurement to monitor students' progress during their clinical skills' training programmes. Furthermore, previous studies showed that the use of virtual reality simulators could provide a better psychomotor learning achievement through the specific pre-clinical task-based courses (Grantcharov 2006;Botden et al 2007;Suksudaj 2010;Urbankova and Engebretson 2011;Tregunna et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These works did not draw attention to the fact that the exercise was not on a tooth or that this may even present a problem. One two-part series of studies (46,47) led to the development of a folded torus-shaped manual dexterity test. Performance based on this shape was found to be discriminatory and could identify students who would require additional support with regard to their fine motor control.…”
Section: Alternatives To Teethmentioning
confidence: 99%
“…In contrast, measuring the functional, perceptual and sensorimotor capabilities of a student has proven to be much more challenging, and there is no consensus on what types of capabilities need to be measured and how they might relate to dentistry. 12 Measurement of these abilities varies substantially across dental schools.…”
Section: Introductionmentioning
confidence: 99%